Meet me at the museum - Youngson, Anne (Black Swan, an imprint of Transworld Publishers, 2019)
Sometimes it takes a stranger to really know who you are. When Tina Hopgood writes a letter of regret to a man she has never met, she doesn't expect a reply. When Anders Larsen, a lonely museum curator, answers it, nor does he. They're both searching for something, they just don't know it yet. Anders has lost his wife, along with his hopes and dreams for the future. Tina is trapped in a marriage she doesn't remember choosing. Slowly their correspondence blossoms as they bare their souls to each other with stories of joy, anguish and discovery. But then Tina's letters suddenly cease, and Anders is thrown into despair.